THE GLOBAL AMBULATORY BLOOD PRESSURE MONITORING (ABPM) IN HEART FAILURE WITH PRESERVED EJECTION FRACTION (HF-PEF) REGISTRY. RATIONALE, DESIGN AND OBJECTIVES. (April 2021) - Camafort, Miguel; Adeseye, Akintunde; Barroso, Weimar Sebba; Coca, Antonio; Damasceno, Albertino; Medina, Angel R. González; Jhund, Pardeep; Kario, Kazuomi; Komori, Takahiro; Lee, Hae -Young; Lip, Stefanie; López-Jaramillo, Patricio; et al.
Abstract : Objective: The prognosis of patients with heart failure and preserved ejection fraction (HFpEF), depends on multiple factors such as frailty and functional capacity, the presence of comorbidities and haemodynamic parameters including blood pressure (BP). Detailed definition of these prognostic factors may help identify effective management strategies. Our primary objective is to identify measures of BP recorded by ambulatory blood pressure monitoring (ABPM) that associated with hospital readmission due to HF or cardiovascular (CV) death, or functional decline in patients with HFpEF. Secondary objectives will be to examine the association between these measures and each of the components of the primary outcome separately and on non-CV death and all cause death, cognitive impairment and frailty. Design and method: In this prospective observational cohort of patients with stable HFpEF, ABPM will be obtained at baseline and at one year of follow-up. Inclusion criteria will be previous diagnosis of stable HFpEF defined as stable treatment or functional class for at least 4 weeks before study admission. A diagnosis of HFpEF (LVEF > 45%) will be made according to the European Society of Cardiology guidelines. In addition to data on demographics and clinical examination, doppler echocardiography, office BP measurement, ABPM recordings, home BP measurement (HBPM), ECG, laboratory tests (serum creatinine, eGFR, Albumin/Creatinine/Ratio, lipid parameters, glucose, HbA1c, liver biology, albumin, prealbumin, blood cell count, ferritin and transferrin saturation rate, natriuretic peptides) will all be recorded. Functional and cognitive capacity will be assessed using the Barthel index and MOCA test, while frailty will be assessed using the Short Physical Performance Battery, and Frail Phenotype questionnaires. Results: We plan to include data from more than 80 investigators from more than 17 countries around the world during the next 5 years. This study has been registered at https://clinicaltrials.gov/ct2/show/NCT04065620 Conclusions: The Global Ambulatory Blood Pressure Monitoring (ABPM) in Heart Failure with Preserved Ejection Fraction (HFpEF) registry will allow us to assess the association between blood pressure and frailty in a global population of patients with HFPEF